Preliminary Assessment of Non-Enzymatic Browning and Antioxidant Activity in Sea Cucumber Derived Gelatin-Sugar Models - Hong, Pui Khoon; Low, Kay May; Moo, Siew Yen; Teh, Yiing Chyn (Trans Tech Publications, 2020)
Four models were developed to assess the development of non-enzymatic browning and antioxidant activity in mixtures of sea cucumber derived gelatin (control), gelatin-glucose, gelatin-fructose and gelatin-glucosamine. All gelatin-sugar models were prepared in mixtures consisted of 5% w/v gelatin and 1.25% w/v sugar and compared against a control (5% w/v gelatin). The mixtures were incubated at 37 °C and 70 °C respectively for up to 24 h. The progress of non-enzymatic browning was monitored via changes in absorption at 280 nm, 320 nm and 420 nm. The gelatin-glucosamine model showed greater development in early Maillard reaction products (280 nm) and pre-melanoidins (320 nm) when incubated at 70 °C after 16 h of incubation. Meanwhile lower incubation temperature (37 °C) promoted browning development (420 nm) in all the models. The gelatin-glucosamine mixture incubated at 70 °C showed high potency in antioxidant activity (p<0.05), this is in accordance to the greater reactivity of glucosamine in the formation of Maillard reaction products at the early and intermediate stages. The results suggested the gelatin-glucosamine model can be further optimized to achieve high potency in antioxidant activity and a desired browning intensity to cater specific applications such as in food and biomaterials.